MO158CLINICOPATHOLOGICAL FEATURES OF COEXISTENT LIGHT CHAIN CASE NEPHROPATHY AND LIGHT CHAIN DEPOSITION DISEASE IN PATIENTS WITH NEWLY DIAGNOSED MULTIPLE MYELOMA. (29th May 2021) - Lin, Zishan; Zhang, Xu; Li, Dan-Yang; Yu, Xiaojuan; Cen, Xinan; Zhou, Fude; Wang, Suxia; Zhao, Minghui
Abstract: Background and Aims: Several patients with multiple myeloma suffered from more than one type of kidney disease simultaneously, of which the most common pattern is coexistent light chain cast nephropathy and light chain deposition disease (LCCN+LCDD). We investigated clinicopathological characteristics of LCCN+LCDD in comparison with pure LCCN and pure LCDD. Method: Forty-seven percent of the renal biopsies revealed a monoclonal κ light chain restriction, ranging from 31% in the pure LCCN group to 90% in the pure LCDD group. Of note, more than half of the patients with LCCN+LCDD showed λ light chain isotype, which was significantly different from patients with pure LCDD (56% vs. 10%, p = 0.033). Compared with patients with pure LCDD, patients with LCCN+LCDD usually presented atypical features of LCDD with less nodular glomerulosclerosis (p = 0.003) and less diffuse deposit distribution (p = 0.027). Compared to patients with pure LCDD, patients with LCCN+LCDD had lower hemoglobin (126.5 g/L vs. 82.0 g/L, p = 0.008), higher incidence of AKI (20% vs. 89%, p = 0.003), lower percentage of urinary albumin excretion (%UAE) (68.9% vs. 5.1%, p = 0.003). There was no significant clinical difference between patients with LCCN+LCDD and patients with pure LCCN. Compared to patients with pure LCDD, patients with pure LCCN had lower hemoglobin (126.5 g/L vs. 87.0 g/L, p = 0.001), higher incidence of AKI (20% vs. 85%, p < 0.001), higher incidence of hemodialysis at diagnosis (10% vs. 65%, p = 0.003), higher serum creatinine (165.8 μmol/L vs. 627.0 μmol/L, p = 0.02) and lower incidence of hematuria (6/10 vs. 4/26, p = 0.035). Results: Forty-seven percent of the renal biopsies revealed a monoclonal κ light chain restriction, ranging from 31% in the pure LCCN group to 90% in the pure LCDD group. Of note, more than half of the patients with LCCN+LCDD showed λ light chain isotype, which was significantly different from patients with pure LCDD (56% vs. 10%, p = 0.033). Compared with patients with pure LCDD, patients with LCCN+LCDD usually presented atypical features of LCDD with less nodular glomerulosclerosis (p = 0.003) and less diffuse deposit distribution (p = 0.027). Compared to patients with pure LCDD, patients with LCCN+LCDD had lower hemoglobin (126.5 g/L vs. 82.0 g/L, p = 0.008), higher incidence of AKI (20% vs. 89%, p = 0.003), lower percentage of urinary albumin excretion (%UAE) (68.9% vs. 5.1%, p = 0.003). There was no significant clinical difference between patients with LCCN+LCDD and patients with pure LCCN. Compared to patients with pure LCDD, patients with pure LCCN had lower hemoglobin (126.5 g/L vs. 87.0 g/L, p = 0.001), higher incidence of AKI (20% vs. 85%, p < 0.001), higher incidence of hemodialysis at diagnosis (10% vs. 65%, p = 0.003), higher serum creatinine (165.8 μmol/L vs. 627.0 μmol/L, p = 0.02) and lower incidence of hematuria (6/10 vs. 4/26, p = 0.035). Conclusion: Pathologically, patients with LCCN+LCDD were more likely to have λ light chain isotype and presented atypical features of LCDD including less nodular glomerulosclerosis and less deposit distribution than patients with pure LCDD. In clinical characteristics, patients with LCCN+LCDD and patients with pure LCCN shared similar features. For patients with LCCD, especially those with λ restriction, nephrologists should carefully evaluate the kidney specimens to exclude the possibility of combined LCCN.